The influence of students’ concept of mole, problem representation ability and mathematical ability on stoichiometry problem solving - Taha, Hafsah; Hashim, Rosnani; Ismail, Zurida; Jusoff, Kamaruzaman; Khoo, Yin Yin (Scottish Group Education and Educating Services, 2014)
Students’ success in stoichiometry problem solving depends mainly on their understanding of the concept of mole and conceptual understanding of the problems. The challenge of enhancing students’ performance in solving stoichiometry problems remain a daunting task as many resort to just teaching how solve stoichiometry problems algorithmically. Two purposes of this study are: first, identifying the major factors influencing students’ performance in stoichiometry problem solving and second, investigating problems faced by students and teachers in stoichiometry learning and teaching in the classroom. A mixed method research design was employed in this study which involved a test and interview protocols. To conclude, students’ understanding of the concept of mole and their problem representation ability are significant predictors, however mathematical ability is not a significant factor in determining students’ success in solving the problems. Students have difficulties in ‘making sense’ of the chemical reaction itself. This implies teachers should not practice the ‘short cut’ approach in the entirety. Students ought to be exposed and guided to understand the underlying conceptual foundation of stoichiometry before introducing the algorithmic way of solving the problems.